How gamification affects switching behaviors in the mobile-commerce platform: the role of customer engagement and switching cost - Yuliawan, Eko; Sanny, Lim; Saroso, Hardijanto; Candra, Sevenpri (Frontiers in Communication, 2025)
This study examines the relationship between gamification in m-commerce and customer switching behavior, with customer engagement as a mediator and switching costs as a moderator. Data was collected using a cross-sectional approach involving 356 respondents in Indonesia. PLS-SEM analysis with moderator variables was applied to test the model and hypothesis. The findings indicate that gamification positively influences customer engagement and negatively affects switching behavior. Additionally, customer engagement has been confirmed to be significantly related to switching behavior and a significant mediator between gamification and switching behavior. Switching costs further moderate the negative relationship between customer engagement and switching behavior. These results provide important implications for business practices and the development of gamification-based customer retention strategies.